2023
DOI: 10.1186/s12913-022-09019-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of community-based health insurance on health service utilization and financial risk protection in Ethiopia

Abstract: Background Evidence on the effectiveness of community-based health insurance (CBHI) in low-income countries is inconclusive. This study assessed the impact of CBHI on health service utilization and financial risk protection in Ethiopia. Methods We conducted a comparative cross-sectional study nested within a larger national household survey in 2020. Data was collected from three groups of households—CBHI member households (n = 1586), non-member hou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Among the higher quality studies, that is, those with low overall risk of bias from RoB 2.0 and ROBINS-I assessments: 10 out of 13 studies, 20 out of 25 studies, and 10 out of 20 studies reported a positive relationship between CBHI enrolment and healthcare utilization, use of outpatient health services, and inpatient hospitalization, respectively. Two high-quality studies, however, reported CBHI enrolment decreased inpatient hospitalization [ 41 , 77 ]. The existing evidence suggests that the government-supported community-involved model had the greatest impact on healthcare utilization– Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the higher quality studies, that is, those with low overall risk of bias from RoB 2.0 and ROBINS-I assessments: 10 out of 13 studies, 20 out of 25 studies, and 10 out of 20 studies reported a positive relationship between CBHI enrolment and healthcare utilization, use of outpatient health services, and inpatient hospitalization, respectively. Two high-quality studies, however, reported CBHI enrolment decreased inpatient hospitalization [ 41 , 77 ]. The existing evidence suggests that the government-supported community-involved model had the greatest impact on healthcare utilization– Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The existing evidence suggests that the government-supported community-involved model had the greatest impact on healthcare utilization– Table 3 . However, the two studies showing a negative impact of CBHI on healthcare utilization were also a government-supported community-involved model in SSA, suggesting that government support in this region could have both favourable and unfavourable effects [ 41 , 77 ]. In addition, the impact of CBHI on healthcare utilization generally improves as the scheme with older schemes– Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The program involved the expansion of healthcare facilities, training of healthcare workers, and the introduction of health insurance schemes to ensure financial access to healthcare services. According to a study by Karema et al (2012), the program has had a significant impact on the health outcomes of Rwandans, particularly in reducing infant mortality rates and improving access to healthcare for vulnerable populations. The study also found that the program has been successful in reducing out-ofpocket healthcare costs for households, which has helped to alleviate poverty in the country.…”
Section: Health Sector Reformmentioning
confidence: 99%
“…The CBHI program aims to alleviate the devastating out-of-pocket medical expenses that affect the 85% of Ethiopians. The goals of CBHI include reducing catastrophic out-of-pocket costs, lowering financial obstacles, increasing the use of health services, enhancing quality of care, enhancing health equity, and enhancing sustainable health finance through mobilization of domestic resources ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%